The effectiveness of promotion mix in commercializing rubber leaves handicraft / Azilahani Mahamad Rabaai - Mahamad Rabaai, Azilahani (Faculty of Business and Management, 2009)
To be successful, organizations must look into the needs and wants of their customers. This is the reason why many researchers have continuously emphasized on the importance of promotion strategy. This will help to increase the sales of the product. Promotion mix which also known as marketing communication can be the best solution in providing information, build customer relationship as well as persuasively communicate customer value.